Sobrecarga em cuidadores familiares de idosos dependentes com vivência comunitária. - Loureiro, Lara de Sá Neves (2011)
Introduction: The aging of population, a phenomenon that has been growing significantly, has led to increasing numbers of elderly patients with damage in their functional capacity. This leads to implications for the health care system and family, because to provide day care for dependent elderly people is a complex and challenging action for these systems, especially to caregivers, due to demand and the provision of care to the elderly, they can express physical and emotional overload. Nevertheless, in our context, studies about this phenomenon are scarce, therefore making this study highly relevant. Objectives: This epidemiological, descriptive and transversal research have as primary objective to estimate the prevalence of burden among family caregivers of elderly who live in the city of João Pessoa and identify possible associations between the burden on caregivers with characteristics of the elderly, the caregivers themselves and the caregiving situation. Methodology: The population studied in the research was of 240 elderly, aged sixty years and older living in Joao Pessoa-PB. Of the sample, 52 elderly with physical and / or cognitive disabilities and their family caregivers were involved (21.6% of the population investigated). To gather the data, a structured instrument was used, focusing on closed questions concerning the study variables, and specific measures to assess, respectively, cognitive and physical ability of elderly and burden among caregivers: mental State Examination, Katz index and Burden Interview Scale. Results: 84.6% of family caregivers of dependent elderly showed overhead. Among them, 72,7% expressed a overload rate between moderate to mild, and 27,3%, moderate to severe. Regarding the elderly who had higher average of overhead we can highlight: those aged 70 to 74 years, male, married, low income and low education, who used the health services of the SUS, lived in multigenerational family structures, with cognitive impairment, reported a higher number of comorbidities and showed a higher level of dependency for basic activities of daily living. In relation to the characteristics of family caregivers that were associated with higher levels of overload, we can highlight: caregivers who were spouses of the care receiver, with advanced age, female, low education, who did not have the help of a secondary caregiver, they had a deficit of knowledge about the need and the forms of care required by elderly and provision of care for long periods of time. Regarding the implications of the caregiving situation, we found significant correlations between the overload and the lack of help to care for the elderly in activities related to the body and oral hygiene, medication and recreation. Conclusion: The results allow us to come in to a conclusion that the burden of family caregivers is a multifaceted and multidimensional phenomenon that requires a different view of the health care system, so they cannot continue concealed in familiar scenario without appropriate and necessary social actions from the public services.